2013
DOI: 10.1097/sih.0b013e318276306e
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of Surgical Skills Laboratories

Abstract: Among surgical residency programs that responded to the survey, most programs schedule time for residents to use a skills laboratory, and most use a curriculum. Those surveyed report that interns derive the most benefit, whereas chief residents derive the least. They also believe that faculty participation is the most important aspect to successful implementation of a skills laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…This finding agrees with previously published work on the effect of PGY on outcomes [4], and may represent an opportunity for better educational objectives, improved intraoperative teaching and supervision, and potentially surgical simulation [27,28]. Recent work has shown that the greatest benefit for surgical simulation and skills laboratory training is derived in the junior years of training [29] and that simulation-models may be an effective tool to improve intra-operative decision-making [30]. These findings must be confirmed prospectively and represent an area of future interest and study.…”
Section: Discussionsupporting
confidence: 90%
“…This finding agrees with previously published work on the effect of PGY on outcomes [4], and may represent an opportunity for better educational objectives, improved intraoperative teaching and supervision, and potentially surgical simulation [27,28]. Recent work has shown that the greatest benefit for surgical simulation and skills laboratory training is derived in the junior years of training [29] and that simulation-models may be an effective tool to improve intra-operative decision-making [30]. These findings must be confirmed prospectively and represent an area of future interest and study.…”
Section: Discussionsupporting
confidence: 90%
“…Responding to the evolving challenges in the surgical training, the Residency Review Committee (RRC) for graduate medical education in the USA requires since 2008 that all residency training programs have to provide surgical residents with access to surgical skills laboratory. Moreover, these facilities must address acquisition and maintenance of skills with a competency-based method of evaluation [36]. Furthermore, the ACS and APDS developed a national skill curriculum in 2007 that is Web-based, is free of charge, and uses proven methods for training, with an emphasis on distributed, deliberate, and structured practice using performance-based end points [37].…”
Section: Skill Acquisition and Deliberate Practicementioning
confidence: 99%
“…Furthermore, the ACS and APDS developed a national skill curriculum in 2007 that is Web-based, is free of charge, and uses proven methods for training, with an emphasis on distributed, deliberate, and structured practice using performance-based end points [37]. The ACS and the society of American gastrointestinal endoscopic surgeons launched the Fundamentals of Laparoscopic Surgery (FLS) which represents the first validated simulation module to be standardized and is now required for surgeons seeking board certification in general surgery in the USA [36,38]. In a recent survey distributed to all residency programs in the USA, 99% of the responders (81 Programs) to the survey had a skill or simulation laboratory [36].…”
Section: Skill Acquisition and Deliberate Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Since the importance of simulation training for the acquisition of surgical skills in a safe environment has become more apparent, the ACGME has stated that surgical residency program resources must include simulation and skills laboratories at teaching hospitals, and they must be used in conjunction with a competency-based method of evaluation (7). A 2013 national survey of surgical skills laboratories conducted in the US demonstrated that 99% of surgical residency programs had a simulation laboratory, 63% of the programs had organized simulation curriculum, and 77% of them utilized the mandated scheduled time for surgical training in the laboratory (9). Successful simulation centers can complement appropriate curriculum M A N U S C R I P T…”
Section: Program Directorsmentioning
confidence: 99%